Predisposing Factors of Scabies among the Patients Attending Skin and Venereal Disease Outdoor of Dhaka Medical College Hospital - Mahmood, Afzalur Rahman; Nur, Zannatun (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> This cross sectional type of descriptive study was carried out among the patients attending the Skin and Venereal Disease (VD) Out Patient Department (OPD) of Dhaka Medical College Hospital (DMCH) from August 2006 to November 2006 with a view to explore the current situation of scabies and its predisposing factors. In this regard 213 clinically diagnosed scabies contracted patients were interviewed randomly by using pre-tested questionnaire. Risk factors were assessed considering their dwelling places, types of families, number of family members, persons living in each room, using fomites of infected persons, socioeconomic condition, occupation, level of education, regular bathing and cloth washing habit along with age, sex distribution and clinical presentation of scabies. The mean age of the respondents was 13.16 years with a standard deviation (SD) of ±5.38 years and majority (36.15%) was in the age group of 1-5 years. Male, female ratio was 1.15:1. Major level of education was in the group of class I to V (38%). 50.73% had family members comprised of 4 to 6. Majority (38.50%) belonged to lower middle class (income 3001-6000 taka/month). Among the respondents maximum (54.93%) were infected by family members. 77.94% respondents used fomites of affected persons and 66% respondents shared beds of infected persons. Mean duration of illness was 42 days with standard deviation of ±4.47 days. Among the male, majority (82.63%) had lesion on lower abdomen and buttock. In contrary, 80.28% female had lesion on hand. 58.68% presented with papule. The study recommends that emphasis should be given on personal hygiene and life style of people as well as educating them about scabies. Key words: Scabies, Predisposing factors, Skin and VD outdoor DOI = 10.3329/jom.v9i2.1436 J MEDICINE 2008; 9 : 82-86